Pengaruh Rekrutmen, Pelatihan, dan Konseling terhadap Produktivitas Kerja Karyawan pada PT. Telkom Akses Medan - Muhammad Nizar Suheil Siregar; Pesta Ria Andriyani; Gregorius Bhima Rhessy Wellan; Sartika Limbong; M Agung Anggoro (Universitas Batanghari Jambi, 2020)
This study aims to determine the effect of the influence of Recruitment, Training and Counseling on Employee Productivity at PT. Telkom Medan access both partially and simultaneously. The research method uses quantitative descriptive analysis. The population in this study were all totaling 462 people. Data analysis techniques using the F Test, T Test, and Multiple Linear Regression. Based on the results of data analysis in this study shows that partially it can be seen that the recruitment variable (X1) has a tcount of 0.837 and a value of 1.663, then the tcount value <ttable (0.837 <1.663) and a sig.0.00 value <0.405. This means the hypothesis is rejected namely: partial recruitment has no positive and significant effect on employee productivity at PT Telkom Akses Medan. The results showed that the training (X2) had a tcount of 3.254 and a t-table value of 1.663, then a tcount> ttable (3.254> 1.663) and a sig value. 0.00 <0.002. This means that the hypothesis is accepted: training has a positive and significant effect on employee productivity in PT Telkom Akses Medan. The results showed that counseling (X3) had a tcount of 2.974 and a t-table value of 1.663 then the tcount> ttabe l (2.974> 1.663) and a sig value. 0.00 <0.004. This means that the hypothesis is accepted: counseling has a positive and significant effect on employee productivity at PT Telkom Akses Medan.